Analysis of Management Procedures and Recording Process of Cash Funds at PT Pusat Dagang Sentosa - Syamsul Arifin; Priyo Utomo (Budapest International Research and Critics University, 2022)
This study aims to determine how to manage and record petty cash at PT Pusat Dagang Sentosa. The data studied are in the form of SOPs for the Finance Accounting Section, Job Descriptions and also financial reports for the April 2020 period. Companies are required to have good and efficient financial performance. Therefore, companies need to have clear and precise SOPs. The method that the researcher uses is descriptive qualitative method by using all secondary data. Based on this research, it is stated thatPetty cash management at PT Pusat Dagang Sentosa is in accordance with the current SOP. It's just that the SOP often changes from time to time to adjust to the running of the company. This resulted in significant changes to the finance work process.